Can Cities Become Sustainable? - Savage, Victor R. (2020)
With 54 percent of the global population of 7.3 billion people living in cities, and the urban population projected in the next 30 years to reach 65 percent of the estimated nine billion people, the question facing governments is whether cities can be sustainable.